2013
DOI: 10.1097/lgt.0b013e3182702796
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Insensitivity Syndrome with Gynandroblastoma and Vulvar Leiomyoma

Abstract: Patients with AIS should be monitored closely because these patients may also experience gonadal tumors. When confronted with gynandroblastoma, close attention should be paid to the patient's endocrinologic status, and comprehensive endocrinologic analyses should be conducted to make correct treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Later similar syndrome was reported by others too [6–9]. Very recently Tian et al reported a case of 64-year-old female (phenotypically) with androgen insensitivity syndrome having bilateral vulval leiomyoma [10]. …”
Section: Discussionsupporting
confidence: 53%
“…Later similar syndrome was reported by others too [6–9]. Very recently Tian et al reported a case of 64-year-old female (phenotypically) with androgen insensitivity syndrome having bilateral vulval leiomyoma [10]. …”
Section: Discussionsupporting
confidence: 53%
“…Most patients presented with a long history of a painless mass. 4 , 12 , 14 , 27 , 28 Because the mass usually remains small (often for 10–20 years) 10 , 12 , 27 and grows slowly in the early period, many patients do not initially see a physician. As the mass increases in size, patients often have difficulty walking, sitting, or having intercourse.…”
Section: Results (Table 1)mentioning
confidence: 99%
“…The most common presentation of vulvar leiomyoma is a painless mass 4 , 12 , 14 , 27 , 28 in the clitoris or labium minora. 24 On physical examination, palpation usually reveals a non-tender mass with firm consistency and partial mobility.…”
Section: Discussionmentioning
confidence: 99%
“…The histogenesis of gynandroblastoma is unknown, but it is generally assumed that it originates from a single progenitor cell that can differentiate into both female and male elements [ 11 ]. During embryogenesis, gonadal tissues develop from the mesoderm of the urogenital ridge and the ridge organizes the endocrinologically active tissues of the gonad, which includes granulosa cells, Sertoli cells, theca cells, ovarian stromal cells, and Leydig cells [ 12 ]. Gynandroblastoma and other sex cord-stromal tumors are considered to have their origin in the cells of the urogenital ridge.…”
Section: Discussionmentioning
confidence: 99%